Leptin up‐regulates TLR2 in human monocytes. Issue 4 (1st April 2013) - Jaedicke, Katrin M.; Roythorne, Ashleigh; Padget, Kay; Todryk, Stephen; Preshaw, Philip M.; Taylor, John J.
Abstract : Leptin‐stimulated TLR2 and CD14 expression may potentiate innate immunity and inflammation, in obesity and T2DM. Abstract : The adipokine leptin elicits changes in the expression of the activation markers CD40 and CD69 in PBMCs and DCs, yet its effect on PRRs remains to be elucidated. Serum leptin concentrations are elevated in obesity and T2DM, which are both diseases associated with a proinflammatory state. We therefore investigated a possible role for leptin in monocyte TLR and CD14 expression. Leptin increased TLR2 cell‐surface and mRNA expression in THP‐1 and primary human monocytes. In contrast, leptin had no effect on monocyte TLR4 expression in THP‐1 or primary monocytes. CD14 cell‐surface and mRNA expression were increased after leptin stimulation in THP‐1 monocytes. However, no change in cell‐surface CD14 expression was observed after leptin treatment in primary human monocytes. Leptin also up‐regulated the expression of PU.1 and EGR2, transcription factors involved in myeloid cell differentiation. Additionally, leptin potentiated Escherichia coli and Porphyromonas gingivalis LPS‐induced TNF‐α secretion in THP‐1 monocytes. In conclusion, we show that leptin and LPS differentially influence monocyte phenotype and demonstrate, for the first time, a regulatory effect of leptin on the monocyte expression of TLR2. Leptin‐stimulated TLR2 expression may potentiate innate immunity and inflammation in conditions of hyperleptinemia, such as obesity and T2DM.